Poisoning event in dogs in an urban area using baits impregnated with aldicarb - Saldeña, Eliana Leticia (2017)
The aim of this study was to implement low complexity methods as butyril cholinesterase activity and thin layer chromatography (TLC) to identify the causal agent of an event that affected 45 poisoned dogs in Mendoza, Argentina. The pesticide identified in the bait extracted from the mouth of a canine was the insecticide carbamate aldicarb, substance with high toxicity, low management safety, with ecotoxicological effects, and with restrictions for its use in Argentina since 1990. Cholinesterase activity levels were indicators of the outcome of the animals.